Effect of reducing the nicotine content of cigarettes on cigarette smoking behavior and tobacco smoke toxicant exposure: 2‐year follow up. (21st July 2015) - Benowitz, Neal L.; Nardone, Natalie; Dains, Katherine M.; Hall, Sharon M.; Stewart, Susan; Dempsey, Delia; Jacob, Peyton
Abstract Background and Aims A broadly mandated reduction of the nicotine content (RNC) of cigarettes has been proposed in the United States to reduce the addictiveness of cigarettes, to prevent new smokers from becoming addicted and to facilitate quitting in established smokers. The primary aim of this study was to determine whether following 7 months of smoking very low nicotine content cigarettes (VLNC), and then returning to their own cigarettes, smokers would demonstrate persistently reduced nicotine intake compared with baseline or quit smoking. Methods In a community‐based clinic 135 smokers not interested in quitting were randomized to one of two groups. A research group smoked their usual brand of cigarettes, followed by five types of research cigarettes with progressively lower nicotine content, each for 1 month, followed by 6 months at the lowest nicotine level (0.5 mg/cigarette) (53 subjects) and then 12 months with no intervention (30 subjects completed). A control group smoked their usual brand for the same period of time (50 subjects at 6 months, 38 completed). Smoking behavior, biomarkers of nicotine intake and smoke toxicant exposure were measured. Results After 7 months smoking VLNC, nicotine intake remained below baseline (plasma cotinine 149 versus 250 ng/ml, P<0.005) with no significant change in cigarettes per day or expired carbon monoxide (CO). During the 12‐month follow‐up, cotinine levels in RNC smokers rose to baseline levels and to those of control smokers. Quit rates among RNC smokers were very low [7.5 versus 2% in controls, not significant). Conclusions In smokers not interested in quitting, reducing the nicotine content in cigarettes over 12 months does not appear to result in extinction of nicotine dependence, assessed by persistently reduced nicotine intake or quitting smoking over the subsequent 12 months.